2016
DOI: 10.1038/srep25312
|View full text |Cite
|
Sign up to set email alerts
|

Co-spread of metal and antibiotic resistance within ST3-IncHI2 plasmids from E. coli isolates of food-producing animals

Abstract: Concerns have been raised in recent years regarding co-selection for antibiotic resistance among bacteria exposed to heavy metals, particularly copper and zinc, used as growth promoters for some livestock species. In this study, 25 IncHI2 plasmids harboring oqxAB (20/25)/blaCTX-M (18/25) were found with sizes ranging from ∼260 to ∼350 kb and 22 belonged to the ST3-IncHI2 group. In addition to blaCTX-M and oqxAB, pcoA-E (5/25) and silE-P (5/25), as well as aac(6′)-Ib-cr (18/25), floR (16/25), rmtB (6/25), qnrS1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
118
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(126 citation statements)
references
References 42 publications
5
118
3
Order By: Relevance
“…S1). ST3-IncHI2 plasmids are reportedly widely disseminated in Chinese poultry and livestock farms, and they carry fosA3, bla CTX-M-9 -group genes (bla CTX-M-14/65/27 ), and/or oqxAB (17,19). In previous studies, ST1-IncHI2 plasmids were associated with bla CTX-M-9 in Europe, while ST2-or APEC-O1-R-type IncHI2 plasmids linked to bla CTX-M-2 were found in Salmonella spp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S1). ST3-IncHI2 plasmids are reportedly widely disseminated in Chinese poultry and livestock farms, and they carry fosA3, bla CTX-M-9 -group genes (bla CTX-M-14/65/27 ), and/or oqxAB (17,19). In previous studies, ST1-IncHI2 plasmids were associated with bla CTX-M-9 in Europe, while ST2-or APEC-O1-R-type IncHI2 plasmids linked to bla CTX-M-2 were found in Salmonella spp.…”
Section: Resultsmentioning
confidence: 99%
“…KT347600.1) (15), bla VIM (accession no. LN555650.1) (16), bla IMP , armA, qnrA, oqxAB, fosA3, and mcr-1 (12,(17)(18)(19)(20)(21). So far, no IncHI2 plasmid carrying bla CTX-M-2 has been characterized fully.…”
mentioning
confidence: 99%
“…The relaxase, with the DNA strand attached, transfers to the recipient cell through the pore formed by the T4SS, finally the plasmid needs to be established in the recipient, with the help of ssDNA binding, anti-restriction and SOS inhibition proteins to generate stable transconjugants. (Alvarez-Martinez and Christie, 2009;Ding and Hynes, 2009;Frost et al, 2005;Koraimann and Wagner, 2014). It is interesting to note that expression of transfer genes is induced in a subset of the bacterial population, maybe diminishing the negative effects of the associated energy cost (Koraimann and Wagner, 2014).…”
Section: Introductionmentioning
confidence: 98%
“…Conjugative plasmids and ICEs from Gram-negative bacteria usually carry all the structural genetic elements required to perform transfer (an oriT site, Dtr and Mpf genes) (Frost et al, 2005). In Gram-positive bacteria, there are two different systems (Goessweiner-Mohr et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, oqxAB-positive IncHI2-ST3 plasmids were mainly reported in this study. Nevertheless, a recent publication reported that most IncHI2-oqxAB-bla CTX-M-9 plasmids in E. coli belong to IncHI2-ST3 (18). It is suggested that the IncHI2 plasmids undergo constant evolvement and dissemination within various bacterial species.…”
mentioning
confidence: 99%